Measurement of low pT D0 meson production cross section at CDF II - Mussini, Manuel <1978> (Alma Mater Studiorum - Università di Bologna, 2011)
In this thesis we present a study of the D0 meson (through one of its two-body decay channel, D0 → Kπ) collected by the CDF II experiment at the Tevatron pp ̄ collider at Fermilab. In particular we measured the differential production cross section as a function of the transverse momentum down to pT = 1.5 GeV/c.